Endovascular procedures versus Open Repair in the management of Abdominal Aortic Aneurysm - Abdelmawla, Mohamed Hassan; El-Baz, Waleed Ali; Abdelrasoul Salama, Ahmed Abo eleinin; Sakr, Abdel Aatti; El-Abeden Mohamed, Abdulaziz Zien (Journal of Neonatal Surgery, 2025)
Background: Endovascular repair or open surgery are two options for treating abdominal aortic aneurysm. To avoid potentially fatal aortic ruptures, prosthesis is inserted in both instances. different research arrived at different findings when trying to determine the best course of treatment. Aim and objectives: Examining the anesthesia, operating time, hospital stay, main patency, and complications of Endo Vascular Aortic Repair (EVAR) vs. open surgical repair (OSR) for infra renal abdominal aortic aneurysms (AAA). Patients and methods: From July 2021 to October 2023, fifty patients at Beni-Sueif University hospital and Military hospitals in Cairo were randomly assigned to either endovascular or open repair of big abdominal aortic aneurysms (≥5.5cm in diameter) in a retrospective observational comparative analysis. Each group consisted of twenty-five patients. Results: The result of study comparing EVAR to open repair is EVAR less in duration of procedure 130-minutes versus 190-minutes for open, less in intraoperative complication 28%for EVAR 52% for open, less in ICU stay 1-day for EVAR versus 3-days for open, less in hospital stay 2-days for EVAR versus 4-days for open. One-week post-operative complications 8% for EVAR 36% for open one-month complications 6% for EVAR 12% for open.one year complications 16% for EVAR and 8% for open. Conclusion: There are a number of advantages to EVAR over traditional surgery, including shorter hospital stays, less blood loss, fewer rates of complications, and rates of inpatient mortality.